2013
DOI: 10.4102/sajim.v15i2.592
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management awareness in a research and development facility: Investigating employee perceptions

Abstract: Background: Research and development (R&D) facilities are dependent on knowledge to develop new and improve existing technologies. R&D employees’ perceptions of the use and management of knowledge are important as these individuals are the source of the innovation needed to generate and develop new processes and services.Objectives: This study aimed to understand Sasol R&D employees’ perceptions of knowledge management (KM). The study also assessed the attitude of Sasol R&D management towards KM.Method: The ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Chang et al [22] claimed that better comprehension of KM improves employees' performance at hospitals. Another study revealed that a positive attitude for KM could give a competitive advantage and can increase innovation [23]. Another supposition is the existence or absence of a correlation between positive perceptions about KM and self-efficacy, as it appears in a sample of librarians in Israel [17].…”
Section: Perceptions About Knowledge Management (Km)mentioning
confidence: 99%
“…Chang et al [22] claimed that better comprehension of KM improves employees' performance at hospitals. Another study revealed that a positive attitude for KM could give a competitive advantage and can increase innovation [23]. Another supposition is the existence or absence of a correlation between positive perceptions about KM and self-efficacy, as it appears in a sample of librarians in Israel [17].…”
Section: Perceptions About Knowledge Management (Km)mentioning
confidence: 99%
“…Empirical studies on KM initiatives in PSOs within the African context include Kimani (2013), Mphahlele (2010), Ncoyini and Cilliers (2016), Ondari-Okemwa (2007), Potgieter, Dube and Rensleigh (2013) and Ramohlale (2014), which showed that although there are no formal structures for managing knowledge in these organisations, a large amount of knowledge flows through them and KM is barely http://www.sajim.co.za Open Access understood in some organisations. However, some organisations regarded KM as important as it has been present for over a decade in the country like South Africa, and several national departments are at various stages of putting KM into practice.…”
Section: Empirical Studies On Knowledge Management Initiatives In The...mentioning
confidence: 99%
“…Empirical studies on KM initiatives in PSOs within the African context include Kimani (2013), Mphahlele (2010), Ncoyini and Cilliers (2016), Ondari-Okemwa (2007), Potgieter, Dube and Rensleigh (2013) and Ramohlale (2014), which showed that although there are no formal structures for managing knowledge in these organisations, a large amount of knowledge flows through them and KM is barely http://www.sajim.co.za Open Access understood in some organisations. However, some organisations regarded KM as important as it has been present for over a decade in the country like South Africa, and several national departments are at various stages of putting KM into practice.…”
Section: Empirical Studies On Knowledge Management Initiatives In The...mentioning
confidence: 99%